Comparison of the Effectiveness of Mindfulness-Based Therapy with Activation of Spiritual-Islamic Schemas and Emotionally Focused Couple Therapy (EFCT) on Resilience, Self-Control, and Marital Adjustment in Couples with a Child with Disabilities - Motalebipour, Seyedeh Ladan; Mirzahoseini, Hassan; Zarghamhajebi, Majid (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to compare the effectiveness of Emotionally Focused Couple Therapy (EFCT) and mindfulness-based therapy with activation of spiritual-Islamic schemas on resilience, self-control, and marital adjustment.Methods and Materials: This research employed a quasi-experimental design with pretest-posttest and a three-group follow-up. The statistical population included all couples with a child with intellectual, physical-motor, or combined intellectual and physical-motor disabilities who were under the support of the Welfare Organization. Using purposive sampling and applying inclusion and exclusion criteria, 48 individuals were initially selected. Then, 16 participants (8 couples) were randomly assigned to the first experimental group, 16 to the second experimental group, and 16 to the control group. A follow-up assessment was conducted three months after the posttest for all three groups. The research instruments included the Dyadic Adjustment Scale (Spanier, 1976) with a Cronbach’s alpha of 0.96, the Tangney Self-Control Scale (Tangney, 2004) with a Cronbach’s alpha of 0.85, and the Connor-Davidson Resilience Scale (Connor & Davidson, 2003) with a Cronbach’s alpha of 0.89. The data were first analyzed using descriptive statistics and then inferential statistics through mixed ANOVA.Findings: The results indicated no significant difference between the effectiveness of mindfulness-based therapy with activation of spiritual-Islamic schemas and EFCT in increasing resilience and self-control (p < .05), although EFCT showed a greater effect on marital adjustment (p < .05). Furthermore, mindfulness-based therapy with activation of spiritual-Islamic schemas had a significant effect on enhancing resilience, self-control, and components of marital adjustment (p < .05). The findings also demonstrated that EFCT significantly improved resilience, self-control, and components of marital adjustment (p < .05).Conclusion: Mindfulness-based and emotion-focused interventions effectively enhance resilience, self-control, and marital adjustment in couples with disabled children, offering culturally sensitive therapeutic approaches aligned with spiritual and emotional needs.